2021
DOI: 10.3389/fpsyg.2021.633433
|View full text |Cite
|
Sign up to set email alerts
|

A Conditional Process Model to Explain Somatization During Coronavirus Disease 2019 Epidemic: The Interaction Among Resilience, Perceived Stress, and Sex

Abstract: BackgroundMore than 15% of Chinese respondents reported somatic symptoms in the last week of January 2020. Promoting resilience is a possible target in crisis intervention that can alleviate somatization.ObjectivesThis study aims to investigate the relationship between resilience and somatization, as well as the underlying possible mediating and moderating mechanism, in a large sample of Chinese participants receiving a crisis intervention during the coronavirus disease 2019 epidemic.MethodsParticipants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…A negative significant relationship was found between the level of stress and psychological resilience (Hou et al, 2017;Zhang et al, 2018;Shangguan et al, 2021;Traunmüller et al, 2021;Yalcin-Siedentopf et al, 2021). However, ELSG and LSG had higher psychological resilience than MSG and EHSG, whereas MSG, HSG, and EHSG did not differ significantly from each other.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A negative significant relationship was found between the level of stress and psychological resilience (Hou et al, 2017;Zhang et al, 2018;Shangguan et al, 2021;Traunmüller et al, 2021;Yalcin-Siedentopf et al, 2021). However, ELSG and LSG had higher psychological resilience than MSG and EHSG, whereas MSG, HSG, and EHSG did not differ significantly from each other.…”
Section: Discussionmentioning
confidence: 84%
“…There was a positive and significant relationship between the level of stress and physiological reactions. They seem to have compensated for a high level of stress that they have perceived through somatization (see Hu and Shao, 2016;Shangguan et al, 2021). Furthermore, standards that MSG, HSG and EHSG have imposed on themselves are higher than ELSG and LSG.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is defined as an ability to recover from stress [ 33 , 34 ]. Shangguan et al [ 35 ] reported that lower resilience is a predictor of somatization, while perceived stress acts as a moderator of resilience and somatization. Perceived stress is more intense and more prevalent among women than among men, revealing a sex-based difference.…”
Section: Relationship Between Children’s Negative Emotions and Posttr...mentioning
confidence: 99%
“…This usually happens due to the extensive and long periods of stressful situations that people experience in events such as natural disasters or wars (Fan et al, 2015). The current pandemic is not an exception and causes a decrease in people's ability to resist, thus, several psychological effects derived from stress are revealed, such as sleep problems (insomnia, early awakening, waking up during the night, nightmares), anxiety, and obsessive-compulsive symptoms (Rojas & Mazón, 2021), somatization disorders (Shangguan, 2021), in addition to worry and suicidal ideation (Killgore et al, 2020) for example.…”
Section: Fear Anxiety and Stress As Risk Factorsmentioning
confidence: 99%